Evaluasi Hasil Belajar Anak Usia Dini Di TK Insan Madani Jln. Laksana No. 100 Medan - Inom Nasution; Ahmad Ardhi Mauluddin Sitorus; Aidatul Fauziah; Era Yunita; Rahmat Efendi; Hasian Rambe (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
Evaluation as a tool and means of assessing how the success rate of the planned program. Each evaluation has different criteria, characteristics and procedures. Procedures for evaluating or assessing early childhood education through the formulation of activities, preparing assessment tools and determining assessment criteria. The results of this study show that the evaluation of early childhood learning carried out by teachers at TK Insan Madani Jln. Laksana No.100 is preceded by compiling a program of activities to be implemented, providing assessments and reporting the results of the assessment to parents. This research uses qualitative methods. Data was obtained from the results of interviews and observations by looking directly at the research site.